Clinical consequences of upfront pathology review in the randomised PORTEC-3 trial for high-risk endometrial cancer. (27th November 2017) - de Boer, S M; Wortman, B G; Bosse, T; Powell, M E; Singh, N; Hollema, H; Wilson, G; Chowdhury, M N; Mileshkin, L; Pyman, J; Katsaros, D; Carinelli, S; et al.
Abstract: Background: In the PORTEC-3 trial, women with high-risk endometrial cancer (HR-EC) were randomised to receive pelvic radiotherapy (RT) with or without concurrent and adjuvant chemotherapy (two cycles of cisplatin 50 mg/m 2 in weeks 1 and 4 of RT, followed by four cycles of carboplatin AUC5 and paclitaxel 175 mg/m 2 ). Pathology review was required before patient enrolment. The aim of this analysis was to evaluate the role of central pathology review before randomisation. Patients and methods: A total of 1295 cases underwent pathology review to confirm HR-EC in the Netherlands ( n  =   395) and the UK ( n  =   900), and for 1226/1295 (95%) matching review and original reports were available. In total, 329 of these patients were enrolled in the PORTEC-3 trial: 145 in the Netherlands and 184 in the UK, comprising 48% of the total PORTEC-3 cohort of 686 participants. Areas of discrepancies were evaluated, and inter-observer agreement between original and review opinion was evaluated by calculating the kappa value ( κ ). Results: In the 1226 pathology reviews, 6356 selected items were evaluable for both original and review pathology. In 43% of cases at least one pathology item changed after review. For 102 patients (8%), this discrepancy led to ineligibility for the PORTEC-3 trial, most frequently due to differences in the assessment of histological type (34%), endocervical stromal involvement (27%) and histological grade (19%). Lowest inter-observer agreement was found for histological type ( κ  = 0.72), lymph-vascular space invasion ( κ  = 0.72) and histological grade ( κ  = 0.70). Conclusion: Central pathology review by expert gynaeco-pathologists changed histological type, grade or other items in 43% of women with HR-EC, leading to ineligibility for the PORTEC-3 trial in 8%. Upfront pathology review is essential to ensure enrolment of the target trial-population, and to avoid over- or undertreatment, especially when treatment modalities with substantial toxicity are involved. This study is registered with ISRCTN (ISRCTN14387080, www.controlled-trials.com ) and with ClinicalTrials.gov (NCT00411138).